INOVASI PEMBELAJARAN PKN KELAS IV MATERI KEBERAGAMAN BUDAYA INDONESIA MELALUI PENERAPAN PROBLEM BASED BERBASIS AJARAN TRI NGA - Indah Pramesti, Riza; Wibawa, Sutrisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education is an effort carried out systematically to acquire knowledge, skills, values ​​and norms from one generation to the next. Apart from aiming to convey information and knowledge, education is intended as a way to develop character and other competencies within students. One of the subjects oriented towards character building in social life is Civics. The learning process must use a learning model that is able to improve critical thinking, collaboration, communication, problem solving skills, and can make the learning atmosphere more fun, active, and encourage students' motivation to learn Civics. Therefore, the influence of the Problem Based Learning (PBL) learning model based on Tri-Nga teachings on Civics learning outcomes is very interesting to study and research. Based on the value of data analysis before implementing the Based Learning (PBL) learning model based on Tri-Nga teachings on the social studies learning outcomes of class IV elementary school students in Gugus 6 Samigaluh, an average value was obtained, namely 67.60. This shows that the average student learning outcomes are in the Low category. Meanwhile, after implementing the Problem Based Learning (PBL) learning model based on Tri-Nga teachings in social studies subjects, the average score was 85.35. This shows that the average student learning outcomes are in the High category. So it can be said that there is an influence of the application of the Problem Based Learning (PBL) learning model based on Tri-Nga teachings on learning outcomes in the Civics subject for class IV elementary school students in Gugus 6 Samigaluh